Long-Term Effect of Charcoal Accumulation in Hearth Soils on Tree Growth and Nutrient Cycling - Mastrolonardo, Giovanni; Calderaro, Chiara; Cocozza, Claudia; Hardy, Brieuc; Dufey, Joseph; Cornelis, Jean-Thomas (Frontiers in Environmental Science, 2019)
There is a lack of long-term field approach investigating biochar impact on soil properties and vegetation, particularly in forest ecosystems. Relic charcoal hearths (RCHs), the result of the historical charcoal production in the forests, preserve a charcoal-enriched topsoil horizon, thus representing a suitable proxy for studying the long-term effect of biochar addition to soil. In this study, we analyzed the chemical properties of a soil as impacted by charcoal accumulation in three RCH plots in southern Wallonia (Belgium) compared to the soil outside RCHs. We further evaluated the effects of RCHs soil properties on the growth performances of silver birch and European beech as well as the leaves’ nutrient concentration of the latter. RCHs soil stored much more carbon and nitrogen than the reference ones. Most of the C in RCHs derived from charcoal (70‒94% of total organic carbon), which would correspond to a total input of 342 tons of biochar per hectare in these soils. Such an accumulation of charcoal still affects nutrient status of soil even after 150 years since charcoal hearths abandonment: CEC and K, Ca, Mg, Na, Mn and Zn concentration remained higher in RCHs soil compared to the reference one. In spite of a seemingly higher fertility of RCHs soil, elemental concentrations of European beech leaves grown in RCHs did not show any significant difference compared to the reference plots, except for C and Mn concentration, higher and lower, respectively, in the leaves of European beech trees grown inside than outside RCHs. Overall, RCHs soil chemical properties were not a decisive factor in significantly improving tree growth. On the contrary, tree ring width average values of both tree species was slightly lower in RCH plots, suggesting to better investigate the potential long-term detrimental effect of a large biochar addition to soil on forest trees.